Ras inhibitor farnesylthiosalicylic acid conjugated with IR783 dye exhibits improved tumor-targeting and altered anti-breast cancer mechanisms in mice - Huang Qiu-ju; Liao Guo-chao; Zhuang Xue-rong; Yang Meng-lan; Yao Jing-jing; Deng Jian-hua; Zhang Yan-min; Wang Ying; Qi Xiao-xiao; Pan Dong-feng; Guan Yang; Huang Zhi-ying; et al. (Acta Pharmacologica Sinica; Vol 43, No 7 (July 2022): Acta Pharmacologica Sinica, 2022)
Ras has long been viewed as a promising target for cancer therapy. Farnesylthiosalicylic acid (FTS), as the only Ras inhibitor has ever entered phase II clinical trials, has yielded disappointing results due to its strong hydrophobicity, poor tumor-targeting capacity, and low therapeutic efficiency. Thus, enhancing hydrophilicity and tumor-targeting capacity of FTS for improving its therapeutic efficacy is of great significance. In this study we conjugated FTS with a cancer-targeting small molecule dye IR783 and characterized the anticancer properties of the conjugate FTS-IR783. We showed that IR783 conjugation greatly improved the hydrophilicity, tumor-targeting and therapeutic potential of FTS. After a single oral administration in Balb/c mice, the relative bioavailability of FTS- IR783 was increased by 90.7% compared with FTS. We demonstrated that organic anion transporting polypeptide (OATP) and endocytosis synergistically drove the uptake of the FTS-IR783 conjugate in breast cancer MDA-MB-231 cells, resulting in superior tumor-targeting ability of the conjugate both in vitro and in vivo. We further revealed that FTS-IR783 conjugate could bind with and directly activate AMPK rather than affecting Ras, and subsequently regulate the TSC2/mTOR signaling pathway, thus achieving 2–10-fold increased anti-cancer therapeutic efficacy against 6 human breast cancer cell lines compared to FTS both in vivo and in vitro. Overall, our data highlights a promising approach for the modification of the anti-tumor drug FTS using IR783 and makes it possible to return FTS back to the clinic with a better efficacy.